Variability in Platelet-Derived Growth Factor Receptor Alpha Antibody Specificity May Impact Clinical Utility of Immunohistochemistry Assays. (December 2016) - Holzer, Timothy R.; O'Neill Reising, Leslie; Credille, Kelly M.; Schade, Andrew E.; Oakley, Gerard J.
Aberrant regulation of the receptor tyrosine kinase platelet-derived growth factor alpha (PDGFRα) is implicated in several types of cancer. Inhibition of the PDGFRα pathway may be a beneficial therapy, and detection of PDGFRα in tumor biopsies may lead to insights about which patients respond to therapy. Exploratory or clinical biomarker use of PDGFRα IHC has been frequently reported, often with polyclonal antibody sc-338. An sc-338-based assay was systematically compared with anti-PDGFRα rabbit monoclonal antibody D13C6 using immunoblot profiling and IHC in formalin-fixed and paraffin-embedded human tumor cell lines. Application of sc-338 to blots of whole cell lysates showed multiple bands including some of unknown origin, whereas application of D13C6 resulted in a prominent band at the expected molecular mass of PDGFRα. The IHC assay using D13C6 showed appropriate staining in cell lines, whereas the assay using sc-338 suggested nonspecific detection of proteins. An optimized IHC assay using D13C6 showed a range of staining in the tumor stromal compartment in lung and ovarian carcinomas. These observations suggest that use of clone sc-338 produced unreliable results and should not be used for an IHC research grade assay. In addition, this precludes its use as a potential antibody for a clinical diagnostic tool.